1984
DOI: 10.1097/00006842-198405000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Hospitalized Cancer Patients

Abstract: The study of depression in cancer patients has been hampered by difficulty in establishing diagnostic criteria, since neurovegetative signs and symptoms may be attributable either to depression or physical illness. Confusion has also arisen in defining the boundary between "normal" grieving with illness, and "abnormal" clinical depression. We studied 62 oncology inpatients applying DSM-III diagnostic criteria, patient self-report, and interview report rating scales. Forty-two percent met criteria for nonbipola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
213
1
18

Year Published

1989
1989
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 531 publications
(245 citation statements)
references
References 17 publications
13
213
1
18
Order By: Relevance
“…Among the medical variables, performance status was the only predictor of fighting spirit. Previous studies have suggested that performance status is one of the most important medical factors affecting psychological distress (Bukberg et al, 1984;Lansky et al, 1985;Cella et al, 1987). This study revealed that measures o1 physical impairment other than cancer site were significantly associated with fighting spirit, suggesting that performance status is among the more important medical factors affecting cancer patients' perception of stress, as opposed to the type of cancer.…”
Section: Discussionmentioning
confidence: 51%
“…Among the medical variables, performance status was the only predictor of fighting spirit. Previous studies have suggested that performance status is one of the most important medical factors affecting psychological distress (Bukberg et al, 1984;Lansky et al, 1985;Cella et al, 1987). This study revealed that measures o1 physical impairment other than cancer site were significantly associated with fighting spirit, suggesting that performance status is among the more important medical factors affecting cancer patients' perception of stress, as opposed to the type of cancer.…”
Section: Discussionmentioning
confidence: 51%
“…One needs to assess the more subtle psychological or cognitive symptoms, such as feeling a lack of pleasure, depressed mood, hopelessness and helplessness along with anxiousness to help establish a diagnosis. 6 AN OVERVIEW OF ANXIETY AND DEPRESSION IN PROSTATE CANCER Anxiety and prostate cancer Anxiety is an affective state that can often occur without an identifiable triggering stimulus. As such, it must be distinguished from fear, which is an emotional response to a perceived threat.…”
Section: General Psychological Issues In Prostate Cancermentioning
confidence: 99%
“…Surpreendentemente, menos da metade dos pacientes com câncer avançado, com sintomas depressivos de moderados a graves, recebe tratamento com antidepressivos 35 . Os cuidadores de pacientes com câncer avançado têm taxas de transtornos psiquiátricos similares aos dos pacientes com câncer avançado.…”
Section: Impacto Da Depressão Na Evolução De Pacientes Com Câncerunclassified